2009
DOI: 10.1021/bc800337d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Novel Bis- and Tris-tetraazamacrocycles for Use in the Copper-64 (64Cu) Radiolabeling of Antibodies with Potential To Increase the Therapeutic Index for Drug Targeting

Abstract: The (64)Cu complexes of a series of mono-, bis-, and tris-tetraazamacrocycles have been prepared, and their stability in human sera has been assessed. The ligands forming the most stable Cu(2+) complexes were then conjugated to the B72.3 antibody (mAb). Conditions for conjugation of the ligands to the mAb were optimized for the concentration of protein, ligand, pH, temperature, and time. The optimum moles of Cu(2+) attached to the mAb were as high as 3.5 for L2 and 5.5 or 2.7 for L5, and the immunoreactivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“… 42 44 In these cases, the functionalized/radiolabeled biomolecule retained affinity for receptor targets in vitro 40 , 41 , 44 and in vivo. 38 , 39 , 42 , 43 Additionally, when compared to bioconjugates containing fewer chelating groups, dendrimer or multichelator conjugated proteins demonstrated higher specific activity—that is, a higher number of radionuclides were bound per bioconjugate compared to homologues containing a single chelator. 38 , 41 43 In some cases, this resulted in higher concentrations of radioactivity at target tissue (tumors) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“… 42 44 In these cases, the functionalized/radiolabeled biomolecule retained affinity for receptor targets in vitro 40 , 41 , 44 and in vivo. 38 , 39 , 42 , 43 Additionally, when compared to bioconjugates containing fewer chelating groups, dendrimer or multichelator conjugated proteins demonstrated higher specific activity—that is, a higher number of radionuclides were bound per bioconjugate compared to homologues containing a single chelator. 38 , 41 43 In some cases, this resulted in higher concentrations of radioactivity at target tissue (tumors) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the novel antibody-dendrimer conjugates with conventionally produced immunoconjugates containing high numbers of single chelating molecules at multiple sites, they found that the number of conjugation sites had a dramatic effect on the immunoreactivity of the antibody, whereas dendrimer size did not influence the immunoreactivity of the derivatized antibody with comparable derivatization sites per molecule. In a recently published study, Ramli et al have designed a tris-tetraazamacrocycle comprising three chelating moieties in order to increase the specific activity of a RIC [17]. In comparison to an analogous mono-tetraazamacrocycle, the tris-tetraazamacrocycle immunoconjugate showed higher specific activity upon radiolabeling with 64 Cu.…”
Section: Introductionmentioning
confidence: 99%
“…However, inappropriate choice in linkage and the local low pH may lead to the detachment of radiometals from NMs in the following cases: 1) The protonation of chelator’s carboxyl and amine groups may compromise the in vivo stability of the chelation ( Figures 1A, i . ( Liu and Edwards, 2001 ; Ramli et al, 2009 ). 2) The newly formed bond between the linkage group of bifunctional chelating agent and the NMs is too weak to maintain stability in vivo (like some ether bonds or ester bonds, Figure 1Aii ).…”
Section: In Vivo Stability Of Radiolabelingmentioning
confidence: 99%
“…1) The protonation of chelator’s carboxyl and amine groups may compromise the in vivo stability of the chelation ( Figures 1A, i . ( Liu and Edwards, 2001 ; Ramli et al, 2009 ).…”
Section: In Vivo Stability Of Radiolabelingmentioning
confidence: 99%